Exome Sequencing of Native Populations From the Amazon Reveals Patterns on the Peopling of South America - Ribeiro-dos-Santos, André M.; Vidal, Amanda Ferreira; Vinasco-Sandoval, Tatiana; Guerreiro, João; Santos, Sidney; Ribeiro-dos-Santos, Ândrea; de Souza, Sandro J. (Frontiers in Genetics, 2020)
Studies on the peopling of South America have been limited by the paucity of sequence data from Native Americans, especially from the east part of the Amazon region. Here, we investigate the whole exome variation from 58 Native American individuals (eight different populations) from the Amazon region and draw insights into the peopling of South America. By using the sequence data generated here together with data from the public domain, we confirmed a strong genetic distinction between Andean and Amazonian populations. Furthermore, a weak Australasian signal was found in two of the populations sequenced here: Araweté and Zo’é. By testing distinct demographic models, our analysis supports a scenario of South America occupation that involves migrations along the Pacific and Atlantic coasts. Occupation of the southeast part of South America would involve migrations from the north, rather than from the west of the continent.